Pulmonary adenocarcinoma in mare - Faccin, Mayane; Cestari, Filipe K.; Matos, Mônica R.; Cavasin, João Pedro; Zimmermann, Anna; Carvalho, Flávio H.; Pagliosa, Geane M.; Viott, Aline M. (Brazilian Journal of Veterinary Pathology, 2018)
Primary lung neoplasms are infrequent in veterinary medicine, particularly in large animals. The most frequently affected species are dogs and cats. These neoplasias are usually malignant and the adenocarcinoma type is the most frequent. This paper describes a case of pulmonary adenocarcinoma in a mare, including its pathological and immunohistochemical features. The animal had natural death and was submitted for necropsy. Diffuse jaundice, splenomegaly due to red pulp hyperplasia, pulmonary edema and congestion were observed. Cytological evaluation of the spleen revealed intracytoplasmatic structures in erythrocytes, compatible with Babesia sp. Histopathology of the lung revealed a neoplastic proliferation of epithelial cells, forming acinar and tubular structures supported by a fibrovascular stroma. Immunohistochemistry of such lesions was positive for cytokeratin and napsin A, negative for vimentin and thyroid transcription factor 1, corroborating the diagnosis of adenocarcinoma. Lung carcinomas in equines are described in animals ranging from four to 23 years old, without breed or sex predisposition. Clinical signs, when present, are related to the compromise of respiratory function, which was not observed in the present case. Pulmonary neoplasms must be considered among the diagnostics of chronic respiratory diseases. Histopathological and immunohistochemistry exams are highly valuable for classification of primary lung neoplasms.